Szansa poprawy sytuacji ekonomicznej ludności powiązanej z rolnictwem na przykładzie województwa mazowieckiego - Chmielewska, Barbara (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Polish integration with the EU created opportunity for improvement of economic situation of fanner families due to direct aid and rural development. In Mazowieckie district this chance was not used in fully because not all of the EU funds for farmhousehold's development and modernization, rural areas' investments and also direct aids and early retirement were used up to the agreed limits. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 242-248